Ecosystem-level impact signals of groundwater borne continental nitrate transfer to the Ria Formosa lagoon by Submarine Groundwater Discharge (SGD) traced along the mixing gradient by a multi-indicator approach - Rocha, C. (2013)
Recognition of the role played by SGD in the transfer of contaminants to near shore marine enviroments underscores the need for tools and aproaches that will facilitate regional assessments of its environmental impact.